Projected Prostate Cancer Incidence in the Middle East by 2050: Socioeconomic Disparities and Future Implications - James Parisi; Yetkin Tuac; Okan Argun; Garrett Kearney; Luke W. Chen; Ozlem Aynaci; Nadeem Pervez; Layth Mula-Hussain; Jonathan E. Leeman; Miranda B. Lam; Mutlay Sayan (JCO Global Oncology)
PURPOSEProstate cancer poses a significant public health challenge in the Middle East, with advanced-stage diagnoses and high mortality rates. However, projections regarding its future incidence are limited. The aims of this study were to estimate prostate cancer incidence in the region through 2050, to evaluate socioeconomic factors contributing to regional disparities, and to provide insights to inform future health care policies and resource allocation.METHODSData from the Global Cancer Observatory were analyzed for Middle Eastern countries, with Europe and North America included for comparison. The percentage change in incidence between 2022 and 2050 was compared across regions using the Mann-Whitney U test. Additional subgroup analyses based on income level and Human Development Index were performed using Kruskal-Wallis test. Spearman rank correlation was used to explore the association between incidence trends and socioeconomic indicators.RESULTSIn 2022, Middle Eastern countries reported 50,944 patients with newly diagnosed prostate cancer, accounting for 3.47% of global incidence. The projected increase in prostate cancer incidence by 2050 was significantly higher in the Middle East compared with Europe and North America (mean rank, 12.50 v 1.50; P = .009). Higher income countries exhibited a greater percentage increase (P = .033), and the income level correlated positively with incidence trends (r = 59.6%; P = .006). Countries with increasing incidence rates had a markedly higher percentage change than those expected to decline (P = .031).CONCLUSIONProstate cancer incidence in the Middle East is expected to rise substantially by 2050, with socioeconomic disparities influencing disease trends. These findings highlight the urgent need for targeted awareness campaigns, improved screening strategies, enhanced oncology infrastructure, and strengthened cancer registries to mitigate the projected burden and improve outcomes in the region.